Cover Picture: Molecular and Interfacial Calculations of Iron(II) Light Harvesters (ChemSusChem 7/2016). Issue 7 (7th April 2016) - Fredin, Lisa A.; Wärnmark, Kenneth; Sundström, Villy; Persson, Petter
Abstract : The Cover Picture shows a dye‐sensitized solar cell with an atomistic perspective of a new class of earth‐abundant iron‐based light‐harvesting complexes capable of achieving efficient photo‐induced interfacial electron injection from the sensitizers to nano‐TiO2 electrodes. An in‐depth computational analysis is used here to elucidate the intrinsic electronic properties of these promising Fe II N‐heterocyclic complexes, in particular providing a detailed theoretical perspective of long‐lived excited states with sufficiently high excited‐state energy to make these complexes viable as molecular sensitizers for solar energy conversion applications. Furthermore, interfacial calculations performed by relaxing an Fe‐carbene adsorbed on a TiO2 nanocluster provides theoretical support for efficient electron injection on ∼100 fs time scales based on a combination of favorable driving force and good interfacial electronic coupling, correlating well with recent experimental findings. More details can be found in the Full Paper by Fredin et al. onpage 667 in Issue 7, 2016 (DOI:10.1002/cssc.201600062 ).